Denitrification using PBS as carbon source and biofilm support in a packed-bed bioreactor - Wu, Weizhong; Yang, Luhua; Wang, Jianlong (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2013)
Biodegradable polymer was used as carbon source and biofilm support for nitrate removal from aqueous solution as an attractive alternative for biological denitrification. The objective of this paper was to investigate the denitrification performance and microbial community of a packed-bed bioreactor using poly (butanediol succinate) (PBS), a biodegradable polymer, as carbon source and biofilm support. NO3-N concentration was determined by UV spectrophotometer. NO2-N concentration was assayed by hydrochloric acid naphthyl ethylenediamine spectrophotometry method. Total organic carbon (TOC) was measured using a TOC analyzer. The morphology of the samples was observed using an environmental scanning electron microscope (ESEM). The microbial community was analyzed by pyrosequencing method. The experimental results showed that an average removal efficiency of nitrate was 95 %. ESEM observation and FTIR analysis indicated the changes of PBS granules before and after microbial utilization. Pyrosequencing results showed that Betaproteobacteria predominated, and most of PBS-degrading denitrifying bacteria were assigned to the family Comamonadaceae. Denitrifying bacteria accounted for 13.02 % in total population. The PBS granules were suitable support and carbon source for denitrifying bacteria.